Application of the Redox‐Transmetalation Procedure to Access Divalent Lanthanide and Alkaline‐Earth NHC Complexes. Issue 50 (29th July 2021) - Schwarz, Noah; Sun, Xiaofei; Yadav, Ravi; Köppe, Ralf; Simler, Thomas; Roesky, Peter W.
Abstract: Divalent lanthanide and alkaline‐earth complexes supported by N‐heterocyclic carbene (NHC) ligands have been accessed by redox‐transmetalation between air‐stable NHC‐AgI complexes and the corresponding metals. By using the small ligand 1, 3‐dimethylimidazol‐2‐ylidene (IMe), two series of isostructural complexes were obtained: the tetra‐NHC complexes [LnI2 (IMe)4 ] (Ln=Eu and Sm) and the bis‐NHC complexes [MI2 (IMe)2 (THF)2 ] (M=Yb, Ca and Sr). In the former, distortions in the NHC coordination were found to originate from intermolecular repulsions in the solid state. Application of the redox‐transmetalation strategy with the bulkier 1, 3‐dimesitylimidazol‐2‐ylidene (IMes) ligand yielded [SrI2 (IMes)(THF)3 ], while using a similar procedure with Ca metal led to [CaI2 (THF)4 ] and uncoordinated IMes. DFT calculations were performed to rationalise the selective formation of the bis‐NHC adduct in [SrI2 (IMe)2 (THF)2 ] and the tetra‐NHC adduct in [SmI2 (IMe)4 ]. Since the results in the gas phase point towards preferential formation of the tetra‐NHC complexes for both metal centres, the differences between both arrangements are a result of solid‐state effects such as slightly different packing forces. Abstract : Redox‐transmetalation is the key : NHC complexes of divalent lanthanides (Sm, Eu, Yb) and alkaline‐earth metals (Ca, Sr) have been accessed by a redox‐transmetalation strategy from NHC‐Ag I complexes, a viable procedure when the classical and non‐redox transmetalation methodology fails to proceed. Trends in the bonding of the NHC ligands were established from a detailed experimental and computational analysis.